Hydro-Diplomacy: Water at the AGE of New Geo-Economic and Geopolitical world Challenges - BOUKARRAS, Roukaia (Journal of Human Sciences, 2024)
Hydro-diplomacy has become a crucial topic in global geo-economic and geopolitical issues, with water at the core of these concerns. This article highlights the increasing importance of water as a strategic resource and the challenges faced by countries worldwide. Water scarcity has become a worrisome reality, driven by population growth, rapid urbanization, and the growing demands of agriculture and industry. This situation creates tensions among nations and potential conflicts over access to and control of water resources. International cooperation in water management is, therefore, essential to prevent potential conflicts. Multilateral agreements and regional initiatives are being implemented to promote cooperation, resource sharing, and peaceful resolution of water-related conflicts.